ANALISIS PENILAIAN KINERJA DENGAN METODE BALANCED SCORECARD PADA ORGANISASAI BISNIS: ANALISIS PENILAIAN KINERJA DENGAN METODE BALANCED SCORECARD PADA ORGANISASAI BISNIS - Ni Wayan Mujiati; A. A Sagung Kartika Dewi; A. A Ayu Sriathi (Forum Manajemen, 2018)
Performance is a level of achievement description from implementationof an activity/ a policy program in achieving target, goal, mission, and vision whichis outlined in strategic planning of an organization. Performance assessment is aperiodically determination of operational effectiveness of an organization, part oforganization and its personnel, based on the target, standard and criteria predefined.Organization is a system consists of cooperation activity pattern which is doneregularly and repeatedly by a group of people to achieve a certain goal. Business isan organized individual business activity to produce and sell goods and services togain profit in fulfilling the people’s needs. Balanced scorecard is a new frameworkto interact various dimensions that are obtained strategy; measuring the companyperformance to four balance perspectives, they are: finance, customer, internalbusiness process and learning and growth.